Enterprise interoperability third international IFIP working conference, IWEI 2011, Stockholm, Sweden, March 23-24, 2011. proceedings - IFIP Working Conference on Enterprise Interoperability 2011 Stockholm, Sweden); Sinderen, Marten van.; Johnson, Pontus; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the proceedings of the Third International IFIP Working Conference on Enterprise Interoperability (IWEI 2011), held in Stockholm, Sweden, March 23-24, 2011. The special theme chosen for IWEI 2011 was Interoperability and Future Internet for Next-Generation Enterprises. Thus special attention was given to how the interoperability needs of enterprises will be shaped and supported by the emerging Future Internet. The 15 papers presented in this volume were carefully selected from 47 submissions, based on a thorough reviewing process in which each paper was scrutinized by at least three experts in the field. The papers cover a wide spectrum of enterprise interoperability issues, ranging from foundational theories, frameworks, architectures, methods and guidelines to applications and case studies. This volume also includes the abstracts of the two invited talks on challenges for future networked enterprise systems.
Electronic reproduction.
Keywords: Internetworking (Telecommunication) -- Congresses; Management information systems -- Congresses; Computer networks -- Congresses; Electronic books